1981
DOI: 10.1093/carcin/2.5.467
|View full text |Cite
|
Sign up to set email alerts
|

Formation of urothelial and hepatic DNA adducts from the carcinogen 2-naphthylamine

Abstract: The carcinogen, 2-naphthylamine (2-NA), induces tumor formation in the urinary bladder but not the liver of several species, including humans and dogs. Since its proximate carcinogenic metabolite, N-hydroxy-2-NA, was known to react directly with DNA in vitro to give specific carcinogen-base adducts, we investigated the in vivo formation and persistence of (2-NA)-DNA adducts in the bladder and liver and attempted to determine whether or not these lesions correlated with tissue susceptibility. Male beagle dogs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…This reduced binding was probably responsible for the small tumor yield being recorded with N-hydroxy-2-NA. The DNA adduct derived from 2-NA in target (urothelium) and nontarget (liver) tissues of dogs have also been reported (10,11). Two days following the oral administration of 2-NA, the same three adducts that were found in vitro from N-hydroxy-2-NA were detected in both tissues with 4-fold higher binding levels being observed in the urothelial DNA.…”
Section: -Naphthylaminementioning
confidence: 85%
See 2 more Smart Citations
“…This reduced binding was probably responsible for the small tumor yield being recorded with N-hydroxy-2-NA. The DNA adduct derived from 2-NA in target (urothelium) and nontarget (liver) tissues of dogs have also been reported (10,11). Two days following the oral administration of 2-NA, the same three adducts that were found in vitro from N-hydroxy-2-NA were detected in both tissues with 4-fold higher binding levels being observed in the urothelial DNA.…”
Section: -Naphthylaminementioning
confidence: 85%
“…When the extent ofbinding was measured 7 days after 2-NA administration, the N2-deoxyguanosine adduct appeared to persist in the dog liver, while both this adduct and the C8-deoxyguanosine adduct persisted in the bladder (10,11). The differential loss of adducts indicates that active repair processes are present in both tissues, and the relative persistence of the C8-deoxyguanosine adduct in target but not in the nontarget tissue suggests that this adduct may be a critical lesion for the initiation of urinary bladder tumors.…”
Section: -Naphthylaminementioning
confidence: 99%
See 1 more Smart Citation
“…This quantitative difference in the metabolism of 1-and 2-naphthylamine is reflected in a similar difference in the level of reaction with DNA in the urothelium. DNAnaphthylamine adducts could be detected in the urothelium (18.5 adducts/108 nucleotides) 2 days after administration of 2-naphthylamine to a dog; but none were detected after administration of 1-naphthylamine (Kadlubar et al, 1981). Because the limit of detection of adducts was 1/108 nucleotides, the magnitude of the difference can only be expressed as at least 18-fold.…”
Section: Discussionmentioning
confidence: 98%
“…Two other bands of radioactivity were detected at 18.5 and 41.0 min. The identity of the early peak is not known; it coeluted with the ribose analogue N-(guanosin-8-yl)-AF and could not be detected after DNA banding on a cesium chloride gradient (27). The (20) indicated that it contained a small amount of highly labeled DNA (=30 ,g DNA per sample; 22 nCi/mg of DNA).…”
Section: Resultsmentioning
confidence: 99%